2014
DOI: 10.4103/2230-8210.137518
|View full text |Cite
|
Sign up to set email alerts
|

A study of bladder dysfunction in women with type 2 diabetes mellitus

Abstract: Introduction:Diabetes mellitus has been associated with an earlier onset and increased severity of urologic diseases that often result in debilitating urologic complications. Diabetic bladder dysfunction refers to a group of bladder symptoms occurring in patients with diabetes mellitus ranging from bladder over activity to impaired bladder contractility.Aim:Bladder dysfunction is an under evaluated issue in women with diabetes. Aim of our study was to investigate prevalence of bladder dysfunction and its relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 24 publications
1
37
2
9
Order By: Relevance
“…Similarly, recent clinical studies also showed the mixed picture of DBD in T2DM patients (Lee et al, 2009; Karoil et al, 2014). Therefore, FVB db/db mouse model is a useful model for further understanding the pathophysiology of T2DM-related bladder dysfunction.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, recent clinical studies also showed the mixed picture of DBD in T2DM patients (Lee et al, 2009; Karoil et al, 2014). Therefore, FVB db/db mouse model is a useful model for further understanding the pathophysiology of T2DM-related bladder dysfunction.…”
Section: Discussionmentioning
confidence: 63%
“…Duration of diabetes has also been shown to be an independent risk factor for OAB. However, the same study noted that glycemic control appeared to have no impact on LUTS or OAB [19].…”
Section: Diabetes and Insulin Resistancementioning
confidence: 94%
“…Another classification of UI is according to the symptoms exhibited by the sufferer, which include: stress incontinence, urge incontinence also referred to as over active bladder (OAB), mixed incontinence which is a combination of the previous two types, unspecified urinary incontinence, functional urinary incontinence, total incontinence, nonorganic enuresis, and urinary incontinence associated with cognitive impairment [3] [6] [7] [8] [9]. The three common types of UI affecting women are stress urinary incontinence, urge incontinence/OAB and mixed incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…The second most common type of UI in women is urge incontinence/OAB as a result of over activity of the detrusor muscles. Common reactions specific to urge incontinence/OAB are frequency, urgency, and nocturia [7]. The third type is the mixed incontinence, which is the presence of both stress incontinence and urge incontinence/OAB in the individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation